Acceptance of Accounting Information System of Cooperative Laboratory - Permatasari, Carolina Lita; Luhsasi, Dwi Iga (Journal of Accounting Science, 2025)
General Background: Accounting information system is an important tool for profit and non-profit organisations, which supports the preparation of financial statements that are critical for managerial decision making. Specific Background: In the domain of behavioural accounting, the emphasis is not only on recording financial transactions but also on understanding how human behaviour affects the interpretation and utilisation of accounting information. Knowledge Gaps: Previous research has identified limited or insignificant effects of perceived ease of use and perceived usefulness on users' interest and intensity in using accounting information systems, indicating a gap in understanding system adoption behaviour. Objective: This study aims to examine the influence of perceived ease of use, perceived usefulness, attitude towards use, and intensity of use on the actual use of co-operative accounting information systems, and to assess user acceptance of such systems in financial reporting. Methods: This study used a quantitative approach with path analysis to evaluate the hypothesised relationships. Results: The findings showed significant positive effects among most of the variables, except for the insignificant effect of perceived ease of use on usage intensity. Novelty: This challenges the basic tenet of the Technology Acceptance Model (TAM), which states that ease of use should drive usage behaviour. Implications: Improving perceived usefulness should be prioritised over simplicity to increase system adoption.